The teacher of new formation: ict teaching insights, values, priorities. (Journal of Educational Sciences, 2016)
As the educational paradigm has changed, educational priorities and learning outcomes have changed as well. The learning outcome is now considered as competence, not knowledge. The competence gives the teacher of new formation the ability to perform skills in different professional and social contexts. The mechanism impacting most positively on educational activities is considered to be ICT technology. This means that ICT as a learning mechanism as a part of inside and outside classroom activities opens new innovative perspectives for both teachers and students. For all this, the issues of axiological, professionally-oriented approaches, teaching values and teaching priorities are discussed in the article. The author tries to put the accent on the development in «the teacher of new formation» professional individuality, creativity, self-reflection and uniqueness in order to raise the prestige of the profession.